Dirāsah Tahlīliyah Linushush Kitāb Ta’lim Allughah Al’arabiyah Lilshafi Altsānī Altsānawī Liwizārah Alsyu`ūn Aldīniyah Al Indūnīsiyah ām 2020 (Alfashl Alrubu’ Hatā Alsādis Namudzajā) - Ahmad Nasrullah; Abdul Rahim (Ukazh: Journal of Arabic Studies, 2022)
This study aims to determine the relevance of the content of the reading text of the secondary school book reading text grade 11, second semester, fourth semester to sixth semester of the Indonesian Ministry of Religious Affairs 2020 issue with the government's core competencies in the 2013 curriculum. This study It is a literary study on the qualitative research method. Literature is studied by means of library data collection, reading, recording, classification data, presentation data, content analysis (content analysis) and data inference (research results). The results of the research proved that the Arabic book for a high school for the eleventh grade of the semester, the fourth to the sixth semester that was published by the Indonesian Religious Ministry in the year 2020, corresponds to the basic competencies of the government in the 2013 school curricula. This can be seen from the content of the article in this book, where It has been formulated and modified with the core competencies of the 2013 curriculum. In this book, from Chapter Four to Chapter Six, four core competencies are gathered that include the domain of spiritual attitudes, social attitudes, cognitive attitude, and skill attitude that are taught in education Penelitian ini bertujuan untuk mengetahui relevansi isi teks bacaan teks bacaan buku sekolah menengah kelas 11 semester dua, semester empat sampai semester enam edisi Kementerian Agama RI tahun 2020 dengan kompetensi inti pemerintah dalam kurikulum 2013 penelitian ini ini adalah studi sastra pada metode penelitian kualitatif. Sastra dipelajari dengan cara pengumpulan data perpustakaan, membaca, merekam, klasifikasi data, penyajian, analisis isi (content analysis) dan data inferensi (hasil penelitian).Hasil penelitian membuktikan bahwa buku bahasa Arab untuk sekolah menengah atas kelas XI semester IV hingga semester VI yang diterbitkan oleh Kementerian Agama RI pada tahun 2020 sudah sesuai dengan kompetensi dasar pemerintah di bidang pendidikan kurikulum sekolah 2013. Hal ini terlihat dari isi artikel dalam buku ini, dimana telah dirumuskan dan dimodifikasi dengan kompetensi inti kurikulum 2013. Dalam buku ini, dari Bab Empat sampai Bab Enam, empat kompetensi inti adalah terkumpul yang meliputi ranah sikap spiritual, sikap sosial, sikap kognitif, dan sikap keterampilan yang diajarkan dalam pendidikan. تهدف هذا الدراسة إلى تحديد مدى ملاءمة محتوى مادة نص القراءة من نص قراءة الكتاب المدرسية الثانوية الصف الحادي عشر، الفصل الدراسي الثاني، الفصل الرابع إلى الفصل السادس من إصدار وزارة الشؤون الدينية الإندونيسية عام 2020 مع الكفاءات الأساسية للحكومة في المناهج الدراسية لعام 2013. هذه الدراسة عبارة عن دراسة أدبية حول منهج البحث النوعي، وتتم دراسة الأدب عن طريق مكتبة جمع البيانات والقراءة والتسجيل وبيانات التصنيف وبيانات العرض والتحليل المحتوى (تحليل المحتوى) واستنتاج البيانات (نتائج البحث).نتائج البحث ثبت أن الكتاب العربية لمدرسة عليا لصف الحادي عشر من الفصل الدراسي، الفصل الرابع إلى السادس الذي نشره الوزارة الدينية الإندونيسية في عام 2020 يتوافق مع الكفاءات الأساسية للحكومة في المناهج الدراسية لعام 2013. ويمكن ملاحظة ذلك من خلال محتوى المادة في هذا الكتاب، حيث تمت صياغته وتعديله مع الكفاءات الأساسية لمنهج 2013. لقد اجتمعت في هذا الكتاب من الفصل الرابع إلى الفصل السادس أربع كفاءات أساسية التي تشمل على مجال المواقف الروحية، والمواقف الاجتماعية، والموقف المعرفية، والموقف المهارية التي يتم تدريسها في التعليم